2008
DOI: 10.1111/j.1462-2920.2007.01519.x
|View full text |Cite
|
Sign up to set email alerts
|

An AbrB‐like protein might be involved in the regulation of cylindrospermopsin production by Aphanizomenon ovalisporum

Abstract: Certain filamentous cyanobacteria, including Aphanizomenon ovalisporum, are potentially toxic owing to the formation of the hepatotoxin cylindrospermopsin. We previously identified a gene cluster in A. ovalisporum likely to be involved in cylindrospermopsin biosynthesis, including amidinotransferase (aoaA) and polyketide-synthase (aoaC), transcribed on the reverse strands. Analysis of the genomic region between aoaA and aoaC identified two transcription start points for each of these genes, differentially expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 65 publications
1
58
0
Order By: Relevance
“…(40). It was suggested by the authors of that work that the posttranslational modifications may affect the structural organization of the protein and thus its affinity for DNA (40). In this work, we also provide evidence of differences between the LexA protein isolated from Synechocystis sp.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…(40). It was suggested by the authors of that work that the posttranslational modifications may affect the structural organization of the protein and thus its affinity for DNA (40). In this work, we also provide evidence of differences between the LexA protein isolated from Synechocystis sp.…”
Section: Discussionsupporting
confidence: 63%
“…The identities of some of the peptides are given on the right. (40). It was suggested by the authors of that work that the posttranslational modifications may affect the structural organization of the protein and thus its affinity for DNA (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of the cyAbrBs was all based on the use of DNA-binding chromatography. Similarly, a cyAbrB that may regulate the production of cylindrospermopsin has been identified in Aphanizomenon ovalisporum (Shalev-Malul et al 2008). Agervald et al (2010) showed that CalA can bind to the regulatory regions of hypC and alr0946(calA)-alr0947.…”
Section: Discussionmentioning
confidence: 99%
“…In cyanobacteria, only a few protein N-terminal acetylation events have been reported, for example, N-terminal acetylation of several proteins such as the Rieske iron-sulfur protein (PetC), Cytochrome b559 subunit beta (psbF) and Photosystem II reaction center protein J (psbJ) [39,74]. N-terminal acetylation of some cyanobacterial peptides [75] or toxins were also reported [76,77].…”
Section: Acetylomementioning
confidence: 99%